2018
DOI: 10.1002/adfm.201805684
|View full text |Cite
|
Sign up to set email alerts
|

Organic Bidirectional Phototransistors Based on Diketopyrrolopyrrole and Fullerene

Abstract: It is shown that simple bilayer devices consisting of the diketopyrrolopyrrole (DPP) monomer Ph‐TDPP‐Ph as donor and C60 as acceptor feature J–V‐characteristics of a bidirectional organic phototransistor where illumination intensity plays the role of the gate voltage as compared to a conventional field‐effect transistor. The output current may therefore be controlled both electrically and optically. The underlying mechanism is based on the good charge transport in Ph‐TDPP‐Ph and C60, the intrinsic dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Encouraged by the bulk-effect merits of our perovskite vertical "optotransistor", we built a logic gate that realized the summation and the subtraction of two optical inputs. 54,55 As shown in Figure 6e, devices 1 and 2 are prepared on the same ITO substrate, and the electrical and S28). When two electric pulses are applied with a bias of (0.7 V, −0.5 V) and (−0.5 V, 0.7 V), the total photocurrent is the difference between the responses of the two components to the light pulses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by the bulk-effect merits of our perovskite vertical "optotransistor", we built a logic gate that realized the summation and the subtraction of two optical inputs. 54,55 As shown in Figure 6e, devices 1 and 2 are prepared on the same ITO substrate, and the electrical and S28). When two electric pulses are applied with a bias of (0.7 V, −0.5 V) and (−0.5 V, 0.7 V), the total photocurrent is the difference between the responses of the two components to the light pulses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The switchable photoconductivity of the diode by light rather than gate voltage allows the device to operate as an optotransistor, which has attracted considerable attention because of its simple structure, high efficiency, and multivalued logic operation. The merit of a transistor is the conductance switching, the turning on and off of the current from the source to drain, which is widely used for logic operation in computing. Encouraged by the bulk-effect merits of our perovskite vertical “optotransistor”, we built a logic gate that realized the summation and the subtraction of two optical inputs. , As shown in Figure e, devices 1 and 2 are prepared on the same ITO substrate, and the electrical and optical signals are applied to the corresponding components. The circuit diagram of the operation circuit is shown in Figure S27, with the total current as the output current.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that Ph-TDPP-Ph adopts two different crystalline phases in thin-film form, with one phase having significantly higher charge carrier mobility (by 2−3 orders of magnitude); however, it was not clear how to process the thin film in order to obtain the phase with the higher carrier mobility. Kahle et al 49 combined Ph-TDPP-Ph and C 60 to fabricate a bidirectional phototransistor that allowed for switching operations with both light and voltage independent from each other, making them applicable as logic elements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 37,67–70 ] Therefore, a number of studies have been performed to obtain both high photo‐sensitivity and fast response time for the next generation photonic devices. [ 71–75 ]…”
Section: Introductionmentioning
confidence: 99%